Enhanced tumor penetration for efficient chemotherapy by a magnetothermally sensitive micelle combined with magnetic targeting and magnetic hyperthermia - Wang, Yu; Wang, Rui; Chen, Lixin; Chen, Lili; Zheng, Yi; Xin, Yuanrong; Zhou, Xiqiu; Song, Xiaoyun; Zheng, Jinzhou (Frontiers in Pharmacology, 2022)
The high accumulation and poor penetration of nanocarriers in tumor is a contradiction of nanomedicine, which reduces the efficacy of chemotherapy. Due to the positive effect of hyperthermia on in vivo drug diffusion, we designed a magnetothermally sensitive micelle (MTM) by integrating magnetic targeting (MT), magnetic hyperthermia (MH), and magnetothermally responsive drug release to facilitate simultaneous drug accumulation and penetration in tumor. Accordingly, we synthesized a cyanine7-modified thermosensitive polymer with phase transition at 42.3°C, and utilized it to prepare drug-loaded MTMs by encapsulating superparamagnetic MnFe2O4 nanoparticles and doxorubicin (DOX). The obtained DOX–MTM had not only high contents of DOX (9.1%) and MnFe2O4 (38.7%), but also some advantages such as superparamagnetism, high saturation magnetization, excellent magnetocaloric effect, and magnetothermal-dependent drug release. Therefore, DOX–MTM improved in vitro DOX cytotoxicity by enhancing DOX endocytosis under the assistance of MH. Furthermore, MT and MH enhanced in vivo DOX–MTM accumulation and DOX penetration in tumor, respectively, substantially inhibiting tumor growth (84%) with excellent biosafety. These results indicate the development of an optimized drug delivery system with MH and MH-dependent drug release, introducing a feasible strategy to enhance the application of nanomedicines in tumor chemotherapy.